Petersen Family Host Private Reception for Mayor of Djambul - Watkins, Howard::::::::: (1989)
Council Member Chris Petersen, wife Chris Petersen, Djambul Mayor, Fresno Mayor Karen Humphrey and husband Ken Clarke